The Atmospheric Corrosion of Structural Steel after Exposure in the Palm Oil Mill Industry Area of Aceh-Indonesia - Muhammad Zulfri; Nurdin Ali; Husaini Husaini; Sri Mulyati; Iskandar Hasanuddin (Universitas Gadjah Mada, 2021)
The major cause of early failure in the infrastructures of the palm oil industry in Aceh, Indonesia has been discovered to be the corrosion caused by air pollution from exhaust fumes of the factory plants. Therefore, this research was conducted to analyze the effect of the atmospheric corrosion of the structural steel used in the palm oil mill industry. The five types of structural steel used as samples include strip, l-shape, round bar, plate, and SAPH 610 low carbon steel with a carbon content of 0.18%. These specimens were cleansed from dirt, scaled, and rubbed with sandpaper to achieve a grid of 600, later washed with fresh water and rinsed with alcohol, and subsequently exposed to the environment in PT ASN and PT AKTS palm oil mills for 12 months. Moreover, they were placed on a measuring tray for exposure and the corrosion rate was recorded once a month using the mass loss method in line with the ASTM G50. The results showed the steel construction with a round bar shape was more resistant to atmospheric corrosion and the remaining samples were also observed to be safe and relatively resistant based on their classification as being outstanding (< 1 mpy).